Overexpression of AtPCS1 in tobacco increases arsenic and arsenic plus cadmium accumulation and detoxification - Zanella, Letizia (Planta, 2015)
The heterologous expression ofAtPCS1in tobacco plants exposed to arsenic plus cadmium enhances phytochelatin levels, root As/Cd accumulation and pollutants detoxification, but does not prevent root cyto-histological damages. High phytochelatin (PC) levels may be involved in accumulation and detoxification of both cadmium (Cd) and arsenic (As) in numerous plants. Although polluted environments are frequently characterized by As and Cd coexistence, how increased PC levels affect the adaptation of the entire plant and the response of its cells/tissues to a combined contamination by As and Cd needs investigation. Consequently, we analyzed tobacco seedlings overexpressing Arabidopsis phytochelatin synthase1 gene (AtPCS1) exposed to As and/or Cd, to evaluate the levels of PCs and As/Cd, the cyto-histological modifications of the roots and the Cd/As leaf extrusion ability. When exposed to As and/or Cd the plants overexpressing AtPCS1 showed higher PC levels, As plus Cd root accumulation, and detoxification ability than the non-overexpressing plants, but a blocked Cd-extrusion from the leaf trichomes. In all genotypes, As, and Cd in particular, damaged lateral root apices, enhancing cell-vacuolization, causing thinning and stretching of endodermis initial cells. Alterations also occurred in the primary structure region of the lateral roots, i.e., cell wall lignification in the external cortex, cell hypertrophy in the inner cortex, crushing of endodermis and stele, and nuclear hypertrophy. Altogether, As and/or Cd caused damage to the lateral roots (and not to the primary one), with such damage not counteracted by AtPCS1 overexpression. The latter, however, positively affected accumulation and detoxification to both pollutants, highlighting that Cd/As accumulation and detoxification due to PCS1 activity do not reduce the cyto-histological damage. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00425-015-2428-8) contains supplementary material, which is available to authorized users.